AN EMPIRICAL STUDY ON THE INFLUENCE OF BUDGET PLANNING AND FINANCIAL ACCOUNTABILITY ON THE PERFORMANCE OF FINANCIAL MANAGERS AT THE OFFICE OF THE MINISTRY OF RELIGION OF MAKASSAR CITY - haeruddin haeruddin; Ibrahim Ahmad2; Muhammad Abbas; Azwar Wijaya Syam; Aigistina Aigistina (Universitas Islam Lamongan, 2024)
The purpose of this study is to determine the influence of budget planning and financial accountability on the performance of financial managers partially and simultaneously. This study uses a quantitative approach. The research population consisted of 41 financial managers in the agency, and the sample was drawn using the saturated sample method. Data collection was carried out through questionnaires designed to measure budget planning variables, financial accountability, and financial manager performance. The collected data will be analyzed using SPSS software, with analysis steps that include descriptive tests to describe the characteristics of respondents, as well as validity and reliability tests to ensure the accuracy of the research instruments. Furthermore, multiple linear regression analysis will be carried out to test the influence of each independent variable on the dependent variable, as well as hypothesis testing through the t-test to determine the individual influence and the F test. Based on the results of this study, it can be concluded that budget planning and financial accountability have a significant influence on the performance of financial managers at the Office of the Ministry of Religion of Makassar City. Good budget planning allows for more efficient allocation of resources and alignment with organizational goals. Meanwhile, accountable financial accountability ensures that every use of the budget can be accounted for, increasing trust and transparency in financial management. Simultaneously, good financial planning and accountability create synergies that have a positive impact on an organization's financial performance, demonstrating that both are key pillars in effective and efficient financial management.